Aplikasi Web Augmented Reality Villa - Pangestu, Gede Yudha Prema; Mandenni, Ni Made Ika Marini; Rusjayanthi, Ni Kadek Dwi (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 5, No. 1 April 2017, 2017)
Bali is one of the highly developed tourist destination in Indonesia. The arrival of tourists having holiday in Bali led to increase residential needs with complete amenities. The occupancy rate of hotel and villa in Bali is increase significantlly during the long vacation. The emergence of new villa and hotel occupancy raises the level of competition in business, so it needs a correct use good marketing communication strategy in marketing the product in order to attract the attention of consumers. Web Application Augmented Reality Villa can help visualize the residential villa in three-dimensional shapes that look more attractive and practical. The use of brochures as written information and the application of augmented reality technology on the Web Application Augmented Reality Villa aims to develop an application that can provide information about the villa to visitors. Web Application uses Augmented Reality Villa designed by FlarToolkit library. Based on the test results show the application can display 3-dimensional objects by scanning marker villa in a brochure which already contain marker.